Economic evaluation of digitally enabled aged and neurological rehabilitation care in the Activity and MObility UsiNg Technology (AMOUNT) trial. (May 2023) - Pinheiro, Marina B; Hassett, Leanne; Sherrington, Catherine; Hayes, Alison; van den Berg, Maayken; Lindley, Richard I; Crotty, Maria; Chagpar, Sakina; Treacy, Daniel; Weber, Heather; Fairhall, Nicola; Wong, Siobhan; et al.
Objective: To investigate the trial-based cost-effectiveness of the addition of a tailored digitally enabled exercise intervention to usual care shown to be clinically effective in improving mobility in the Activity and MObility UsiNg Technology (AMOUNT) rehabilitation trial compared to usual care alone. Design: Economic evaluation alongside a pragmatic randomized controlled trial. Participants: 300 people receiving inpatient aged and neurological rehabilitation were randomized to the intervention ( n  = 149) or usual care control group ( n  = 151). Main measures: Incremental cost effectiveness ratios were calculated for the additional costs per additional person demonstrating a meaningful improvement in mobility (3-point in Short Physical Performance Battery) and quality-adjusted life years gained at 6 months (primary analysis). The joint probability distribution of costs and outcomes was examined using bootstrapping. Results: The mean cost saving for the intervention group at 6 months was AU$2286 (95% Bootstrapped cost CI: −$11, 190 to $6410) per participant; 68% and 67% of bootstraps showed the intervention to be dominant (i.e. more effective and cost saving) for mobility and quality-adjusted life years, respectively. The probability of the intervention being cost-effective considering a willingness to pay threshold of AU$50, 000 per additional person with a meaningful improvement in mobility or quality-adjusted life year gained was 93% and 77%, respectively. Conclusions: The AMOUNT intervention had a high probability of being cost-effective if decision makers are willing to pay AU$50, 000 per meaningful improvement in mobility or per quality-adjusted life year gained, and a moderate probability of being cost-saving and effective considering both outcomes at 6 months post randomization.